RELATIONSHIP BETWEEN FASTING BLOOD GLUCOSE LEVELS AND LDL CHOLESTEROL LEVELS IN PATIENTS WITH TYPE-2 DIABETES MELLITUS IN DIPONEGORO NATIONAL HOSPITAL - Muhammad Fakhrul Aditya Duta Pradana; Edward Kurnia Setiawan Limijadi; Kusmiyati Tjahjono; Banundari Rachmawati (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Background: Diabetes Mellitus is a chronic metabolic disorder characterized by elevated blood glucose levels above the normal range. Type-2 diabetes mellitus can cause lipid metabolism disorder. This study analyzed the relationship between fasting blood glucose and LDL cholesterol levels in type-2 diabetes mellitus patients.Aim: To prove the correlation between fasting blood glucose levels with LDL cholesterol levels in patients with type-2 diabetes mellitus.Methods: This research is an observational analytical study with cross-sectional design on 40 subjects. The secondary data for this research was obtained from diabetic patients at Diponegoro National Hospital. The correlation analysis was done using Spearman Rank test.Results: Spearman Rank analysis showed no significant association between fasting blood glucose levels with LDL cholesterol levels in patients with type-2 diabetes mellitus (p = 0,119 and r = 0,250).Conclusion: There was no significant correlation between fasting blood glucose levels with LDL cholesterol levels in patients with Type-2 Diabetes Mellitus.